Hausmeister : Report of Worldwide Visual Diseases 2000. - Unwahr Gallery, Berlin; Ayers, David; Bayer, Konrad; Cullen, Shane; Haerdter, Michael; Hager, Michael; Heidenreich, Stefan; Heisterkamp, Fritz; Matta-Clark, Gordon; Sexton, John; Skapski, Lukasz (Berlin : [s.n.], 1995)
Ayers, David ; Bayer, Konrad ; Cullen, Shane ; Haerdter, Michael ; Hager, Michael ; Hausmeister, Stephan ; Heidenreich, Stefan ; Heisterkamp, Fritz ; Jolley, Paddy ; Matta-Clark, Gordon ; Murray, Paul ; Sakpski, Lukasz ; Sexton, John ; Vergara, Camilo Jòse
Artist book : Producer : Stephan Hausmeister
biog. [7 p.]
Hausmeister : Pathologische Aspekte der Gegenwartskunst, Unwahr Gallery, Berlin, 1995-04-15
Duits
Duits & Engels
Engels
Keywords: Hausmeister, Stephan